ENHANCE OF ONLINE FINANCIAL E-COMMERCE - Dorin, Julia (Proceedings Of The International Seminar, 2022)
The research aims to determine the financial performance of online credit companies for tax revenues in Indonesia. The data used is the data of registered Financial Technology (Fintech) and not registered in Otoritas Jasa Keuangan (OJK). The data analysis method used in this research is a quantitative descriptive analysis. The results of the research are the development of Financial Technology is impressive and impact on the company's cash increase. The number of interests of customers chose the company and made increased tax revenue in Indonesia, but the Financial Services Authority or OJK must be firmly in the handling of Financial Technology (Fintech) companies that are not registered for Customer trust in the future.   Keywords: Financial Performance, Online Credit, Tax